Morbidity profile of truck drivers: a South Indian cross-sectional study - Mathew, Anil C.; Veyilmuthu, Ramamoorthy; Palanisamy, Subash; Vargheese, Xavier Christu Rajan (International Journal Of Community Medicine And Public Health, 2019)
Background: Recent studies have shown that workers on the transport industry are more predisposed to cardiovascular morbidity and other health morbidities due to their improper diet and sedentary lifestyle. This study was aimed at assessing the common morbidity profile among the truck drivers and associated demographic and clinical parameters considered relevant to the development of cardiovascular disease. Methods: This was a cross sectional study conducted among 175 truck drivers aged 18-60 years at the Walayar check post, Coimbatore, southern India. After getting informed consent, a detailed physical examination was conducted. Socio demographic information was also elicited. Results: It was observed that 50% of the truck drivers were overweight and obese. Hypertensives were 41.1% and diabetics were 12%. About 27.4% had raised systolic blood pressure (BP) and 29.1% had raised diastolic BP. Low back pain was observed in 34.3%, hip pain in 24.6%, knee pain in 9.7%, shoulder pain in 5.4%, diminished vision in 4.6%, giddiness in 2.3% and hearing defects in 1.1% of the truck drivers.56.6% were current smokers and 66.3% were taking alcohol consumption more than 4 times a month. Older age was found to be a significant independent predictor [odds ratio OR 1.04 (95% CI 1.03-1.05)] for the total number of cardio vascular disease morbidities. Conclusions: We observed a higher morbidity among the truck drivers and observed that periodic health appraisals are needed.